Comparing Anatomical and Functional Outcomes of Two Neovaginoplasty Techniques for Mayer-Rokitansky-Küster-Hauser Syndrome: A Ten-Year Retrospective Study with Swine Small Intestinal Submucosa and Homologous Skin Grafts - Xu H; Hou S; Ruan Z; Liu J (Dove Medical Press, 2023)
Hui Xu, Shuhui Hou, Zhengyi Ruan, Jianhua Liu Department of Obstetrics and Gynecology, Shanghai Ninth People's Hospital, School of Medicine, Shanghai Jiaotong University, Shanghai, People's Republic of ChinaCorrespondence: Zhengyi Ruan; Jianhua Liu, Department of Obstetrics and Gynecology, Shanghai Ninth People's Hospital, School of Medicine, Shanghai Jiaotong University, No. 639, Zhi Zaoju Road, Shanghai, 200011, People's Republic of China, Email ruan19800616@163.com; Drliu.2006@aliyun.comObjective: This study aimed to compare the anatomical and functional outcomes of the modified McIndoe vaginoplasty for Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome using swine small intestinal submucosa (SIS) graft or homologous skin grafts.Methods: A total of 115 patients with MRKHs who underwent neovaginoplasty between January 2012 and December 2021 were included in the study. Among them, 84 patients received vaginal reconstruction with SIS graft, whereas 31 neovaginoplasty underwent a skin graft procedure. The length and width of the neovagina were measured, and sexual satisfaction was evaluated using the Female Sexual Function Index (FSFI). The operation details, cost, and complications were also assessed.Results: The SIS graft group had a significantly shorter mean operation time (61.13± 7.17min) and less bleeding during the operation (38.57± 9.46mL) compared to the skin graft group (92.1± 9.47min and 55.81± 8.28mL, respectively). The mean length and width of the neovagina in the SIS group were comparable to the skin graft group at 6 months follow-up (7.73± 0.57 cm versus 7.6± 0.62cm, P=0.32). The SIS group had a higher total FSFI index than the skin graft group (27.44± 1.58 versus 25.33± 2.16, P=0.001).Conclusion: The modified McIndoe neovaginoplasty using SIS graft is a safe and effective alternative to homologous skin grafts. It results in comparable anatomical outcomes and superior sexual and functional outcomes. Overall, these results suggest that the modified McIndoe neovaginoplasty using SIS graft is preferred for MRKH patients who require vaginal reconstruction.Keywords: neovaginoplasty, Mayer-Rokitansky-Küster-Hauser syndrome, skin graft, swine small intestinal submucosa biological graft